PKCδ is dispensible for oxLDL uptake and foam cell formation by human and murine macrophages. (24th September 2014) - Szilagyi, Katka; Meijer, Alexander B.; Neele, Annette E.; Verkuijlen, Paul; Leitges, Michael; Dabernat, Sandrine; Förster-Waldl, Elisabeth; Boztug, Kaan; Belot, Alexandre; Kuijpers, Taco W.; Kraal, Georg; de Winther, Menno P. J.; et al.
Abstract: Aims: Uptake of oxidized lipoprotein particles (oxLDL) and foam cell formation by macrophages is one of the first steps in the development of atherosclerosis. Recently, protein kinase C δ (PKCδ) has been implicated as a regulator of oxLDL uptake and foam cell formation via down-regulation of PKCβ and scavenger receptors CD36 and SR-A expression. Here, we describe studies in which we have re-evaluated the role of PKCδ in oxLDL uptake and foam cell formation. Methods and results: PKCδ expression was silenced in the human monocytic cell lines and also in primary human monocytes to analyse oxLDL uptake and CD36 expression. Additionally, bone marrow-derived macrophages of PKCδ knockout mice and macrophages cultured from patients with rare null mutations in the PRKCD gene were tested for uptake of oxLDL and foam cell formation. Expression of scavenger receptor CD36 was determined and levels of PKCβ isoforms were quantified. Neither a reduction in PKCδ levels nor its complete absence resulted in a detectable effect on the uptake of oxLDL and the formation of foam cells. Conclusion: PKCδ is dispensible for oxLDL uptake and foam cell formation by monocytes and macrophages.